2019
DOI: 10.3389/fonc.2019.00400
|View full text |Cite
|
Sign up to set email alerts
|

TIPE1 Inhibits Breast Cancer Proliferation by Downregulating ERK Phosphorylation and Predicts a Favorable Prognosis

Abstract: TIPE1, which acts as a cell death regulator, has emerged as a tumor suppressor in the process of carcinogenesis. However, our recent research demonstrated that it serves as an oncogene in the pathogenesis of cervical cancer, indicating that the role of TIPE1 in carcinogenesis needs to be further evaluated. In this study, we show that TIPE1 is able to inhibit breast cancer cell growth both in vivo and in vitro . Functionally, TIPE1 inhibits cancer cell proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
(36 reference statements)
2
10
1
Order By: Relevance
“…Our previous studies found that TIPE1 was downregulated in hepatocellular carcinoma which could induce caspase-mediated apoptosis and inhibit HCC cell growth both in vitro and in vivo [ 6 ]. Similar results were confirmed and presented in lung cancer [ 7 ], gastric cancer [ 8 ], osteosarcoma [ 9 ], breast cancer [ 10 , 11 ], and colorectal cancer [ 12 ]. A recent study reported that TIPE1 was decreased in tissue microarrays and inhibited proliferation through inducing apoptosis in ovarian cancer cells [ 13 ], but whether TIPE1 related to tumor metastasis was not mentioned.…”
Section: Introductionsupporting
confidence: 81%
“…Our previous studies found that TIPE1 was downregulated in hepatocellular carcinoma which could induce caspase-mediated apoptosis and inhibit HCC cell growth both in vitro and in vivo [ 6 ]. Similar results were confirmed and presented in lung cancer [ 7 ], gastric cancer [ 8 ], osteosarcoma [ 9 ], breast cancer [ 10 , 11 ], and colorectal cancer [ 12 ]. A recent study reported that TIPE1 was decreased in tissue microarrays and inhibited proliferation through inducing apoptosis in ovarian cancer cells [ 13 ], but whether TIPE1 related to tumor metastasis was not mentioned.…”
Section: Introductionsupporting
confidence: 81%
“…Recently, Ye et al ( 26 ) reported that ectopic TIPE1 expression efficiently impairs stemness in colorectal cancer both in vitro and in vivo . TIPE1 also inhibits breast cancer cell proliferation, both in vivo and in vitro ( 27 ), whereas it serves as an oncogene in the pathogenesis of cervical cancer ( 17 ). Furthermore, TIPE1 overexpression effectively inhibits osteosarcoma tumor growth in vivo , which may contribute to the inhibition of macrophage infiltration in osteosarcoma ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that TIPE1 can inhibit cell growth and induce cell death in several types of cancer. Supporting this, our group also found that TIPE1 inhibits breast cancer proliferation by inhibiting the ERK pathway ( 7 ). However, we recently demonstrated that TIPE1 significantly induces cell proliferation and tumor burden in cervical cancer ( 6 ).…”
Section: Tipe1 Enhances Cervical Cancer Chemoresistance In a Wild-typmentioning
confidence: 70%